Revitalization of the Indonesian Librarian Association’s Roles in Supporting Library Professionalism - Muh. Quraisy Mathar (Program Studi Ilmu Perpustakaan UIN Alauddin, 2022)
This study gives a brief history of the founding of the Indonesian Librarian Association, the umbrella organization for the librarian profession, which, to this day, continues to discover its optimal structure in cooperation with the study of library science, which produces future librarians (alumni). Some other professional organizations are used in this study as equivalent comparative institutions to clarify the realities surrounding the functions of the Indonesian Librarian Association. In order to build the ideal structure for a professional organization, this research is intended to offer a new foundation for reviving or reconstructing the roles and interdependence of the Indonesian Librarian Association with all linked organizations, either directly or indirectly.